Assessment of solubilization characteristics of different surfactants for carvedilol phosphate as a function of pH - Chakraborty S.; Shukla D.; Jain A.; Mishra B.; Singh S. (My University, 2025)
The effect of surfactants on the solubility of a new phosphate salt of carvedilol was investigated at different biorelevent pH to evaluate their solubilization capacity. Solutions of different classes of surfactants viz., anionic-sodium dodecyl sulfate (SDS) and sodium taurocholate (STC), cationic-cetyltrimethylammonium bromide (CTAB) and non-ionic-Tween 80 (T80) were prepared in the concentration range of 5-35 mmol dm-3 in buffer solutions of pH 1.2, 3.0, 4.5, 5.8, 6.8 and 7.2. The solubility data were used to calculate the solubilization characteristics viz. molar solubilization capacity, water micelle partition coefficient, free energy of solubilization and binding constant. Solubility enhancement in basic pH was in following order: CTAB > T80 > SDS > STC. CTAB and T80 showed remarkable solubility enhancement in acidic pH as well. Among the anionic surfactants, solubility in acidic medium was retarded except at pH 1.2 in case of SDS. Cationic and non-ionic surfactants were found to be suitable for enhancing the solubility of CP which can be employed for maintaining the in vitro sink condition in the basic dissolution medium. While anionic surfactants showed solubility retardant behavior which may be exploited in increasing the drug entrapment efficiency of a colloidal drug delivery system formulated by emulsification technique. © 2009 Elsevier Inc. All rights reserved.